Biodiversity of Fishes of River Ecosystems of the Western Tyan-Shan - Mirzaev, Ulugbek (RA Journal of Applied Research, 2021)
The paper cites data on the biological diversity of fishes in the river ecosystems of the Western Tien Shan. Data on the diversity and distribution of species are presented and analyzed. The role of various factors affecting the variability of species numbers and their range is discussed, which is important for development of a number of measures on conservation of rare and vanishing fish species.